Metastatic anorectal malignant melanoma causing ileocaecal junction obstruction due to contiguous spread - Deshpande, Swanit Hemant (BMJ Case Rep, 2021)
Malignant melanoma of the anal canal is a rare and aggressive tumour associated with significant mortality. Early diagnosis and early curative surgical resection have shown to offer a survival advantage. We present a case of 53-year-old woman, who was accidentally diagnosed to have a localised lesion of malignant melanoma of the anal canal on histopathology report of the specimen of haemorrhoidectomy done for thrombosed external haemorrhoids. She refused any form of treatment and did not return for follow-up. Two years after the initial diagnosis, she presented with intestinal obstruction. The malignant melanoma had become advanced with multiple metastases to the lungs, the liver, the peritoneum and the spine. The patient underwent a diverting loop ileostomy. At the time of surgery, it was found that the primary malignant melanoma of anal canal had contiguously involved the entire large intestine up to the ileocaecal junction and hence transverse colostomy could not be done.